The Effect of Emotional Intelligence and Social Support on Student Learning Outcomes at SMK Negeri 1 Bukal - Ostin Usman; Nur Ayu Winingsih (Journal of Educational Technology and Innovation, 2025)
This study aims to determine the influence of emotional intelligence and social support on student learning outcomes at SMK Negeri 1 Bukal. In the context of vocational education, student learning outcomes are not only influenced by cognitive abilities, but also by psychosocial factors such as emotional intelligence and social support. The research method used is a quantitative approach with a correlational design. The research sample amounted to 53 students who were selected through proportional random sampling techniques. The research instruments include emotional intelligence and social support questionnaires as well as documentation of student learning outcomes. Data analysis was carried out using multiple linear regression. The results showed that emotional intelligence had a positive and significant effect on student learning outcomes (p < 0.05), while social support had a positive but not statistically significant effect (p > 0.05). These findings affirm the importance of strengthening emotional aspects in students to improve academic performance, as well as the need to pay attention to social support as a complement to a conducive learning environment. This research makes a theoretical and practical contribution to the development of holistic educational strategies that integrate cognitive, emotional, and social dimensions, especially in rural vocational schools.